Patterns in the electrochemical synthesis of thin-film photocatalytic materials based on titanium heterooxide compounds - Sakhnenko, Mykola; Stepanova, Iryna; Korogodskaya, Alla; Karakurkchi, Ann; Skrypnyk, Olena; Dzheniuk, Anatoly; Halak, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2022)
This paper reports a study the into processes of plasma-electrolyte formation of heterooxidic coatings on titanium alloys for the photocatalytic destruction of natural and man-made toxicants. The synthesis of coatings was carried out from aqueous solutions of diphosphates under a galvanostatic mode. For a quantitative description of photocatalytic reactions, the constants of the reaction rate kf from the linearized dependences ln(Ct/C0), where Ct is the current, C0 is the initial concentration of the reagent, were calculated. The morphology of the coating surface was investigated by atomic force microscopy, and the results were visualized by reconstruction of the relief in the form of 2D and 3D topographic maps. Morphological features of coatings made of titanium oxide (IV) and heterooxidic composites containing oxides of transition metals were analyzed. It is shown that the specific surface area remains an effective factor in regulating the photocatalytic activity of coatings. The establishment of the morphology of heterooxidic composites, as well as methods for controlling this parameter of the target product, is a constant component of the systematic study of such materials in determining their functional properties. It has been established that compared to oxide-titanium coatings whose surface layers are characterized by a toroidal mesostructure, heterooxidic compositions have a more developed surface, which has a positive effect on their functional properties. Subsequent heat treatment similarly affects the properties of the coating. The speed constants of the photocatalytic decomposition of the methyl yellow-hot azo dye were used to rank coatings of different composition according to their functional properties. Coatings from TiO2·ZnO showed the highest catalytic activity among the materials studied – kf is 5.26 10-3 min-1, which is several times higher than the corresponding value for TiO2